2021
DOI: 10.1007/s10508-020-01891-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution Policies and Attitudes Toward Prostitutes

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For example, item A4 (Sexual relations outside the context of marriage are always wrong) did not reach consensus and was subsequently removed; however, this may be an important item depending on the cultures and nations where in the instrument is used (Cipriani et al 2016;Henrickson et al 2021). Similarly, involvement with sex services is legalised in some nations but against social norms in others (Bonache et al 2021). Nevertheless, cultures, nations and attitudes towards sexual expression can be influenced by personal religious views (Gewirtz-Meydan, Even-Zohar, and Werner 2018) and perceptions of sexual relations between couples might vary (Labrecque and Whisman 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, item A4 (Sexual relations outside the context of marriage are always wrong) did not reach consensus and was subsequently removed; however, this may be an important item depending on the cultures and nations where in the instrument is used (Cipriani et al 2016;Henrickson et al 2021). Similarly, involvement with sex services is legalised in some nations but against social norms in others (Bonache et al 2021). Nevertheless, cultures, nations and attitudes towards sexual expression can be influenced by personal religious views (Gewirtz-Meydan, Even-Zohar, and Werner 2018) and perceptions of sexual relations between couples might vary (Labrecque and Whisman 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, involvement with sex services is legalised in some nations but against social norms in others (Bonache et al. 2021). Nevertheless, cultures, nations and attitudes towards sexual expression can be influenced by personal religious views (Gewirtz‐Meydan, Even‐Zohar, and Werner 2018) and perceptions of sexual relations between couples might vary (Labrecque and Whisman 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Switching focus, Silver et al (2015) did go beyond individual differences in the evaluator to explain judgments about survivors by presenting a vignette in which a woman engaged in sex work either forcibly or voluntarily and found that participants rated the trafficked woman less responsible for her behavior, but only when she was a citizen and not when she was an immigrant. Finally, Bonache et al (2021) focused on moral judgments and presented a scenario to Spanish participants about sexual exploitation and found that participants expressed higher moral outrage toward the exploited individual when they were trafficking victims as compared to when they voluntarily engaged in prostitution as a means of employment (Note: Sex work is not illegal in Spain). In summary, while these studies highlight the importance of understanding the roles of attitudes, cognitions, and background characteristics as potential antecedents of blaming trafficking victims and therefore as barriers to a victim-centered approach, none have studied decision models that observers likely use to translate facts into psychological reactions and ultimately culpability judgments.…”
Section: The Psychology Of Judgments Of Trafficking Responsibilitymentioning
confidence: 99%